Pengaruh Determinan Minat Mahasiswa Mengikuti Program Brevet Pajak dan Dampaknya Terhadap Pemilihan Karir di Bidang Perpajakan: Studi Empiris pada Mahasiswa Akuntansi Universitas Jambi - Velindi Simarmata, Yana; Tiswiyanti, Wiwik; Wiralestari (Masyarakat Ekonomi Syariah Bogor, 2024)
This study aims to analyze and find empirical evidence regarding the determinants that influence students' interest in participating in the tax brevet program and its impact on career choices in the field of taxation. This research is a questionnaire-based study, which is a quantitative method using primary data. The population in this study consists of Accounting students from Jambi University, specifically those from the 2019, 2020, and 2021 cohorts, totaling 514 students. The sampling technique used is purposive sampling with the Slovin formula to determine the sample size. The sample used consisted of 175 respondents obtained through the distribution of online questionnaires. Based on data processing using PLS, it was found that motivation and financial rewards influence accounting students' interest. Similarly, students' interest in participating in the tax brevet program has an impact on their career choices in the field of taxation. Meanwhile, the social environment and education costs do not influence students' interest in participating in the tax brevet program